Pilomatrixoma in crossbred dog (Canis lupus familiaris) in Arequipa, Peru - Fernández F., Fernando (2022)
The case of a 4-year-old crossbred female canine patient with pilomatrixoma, a benign neoplasm derived from hairy matrix cells, is detailed.